Increasing Community Participation in Controlling Space Utilization Through A Youth Generation Capacity Building Approach in Makassar City - Arifuddin Akil; Ananto Yudono; Sri Wahyuni (Faculty of Engineering UNHAS, 2023)
Spatial utilization is an effort to realize the spatial structure and spatial pattern in accordance with the spatial plan through the preparation and implementation of programs and their financing. In order to create an orderly spatial layout, it is necessary to control the use of space in all urban areas. The effectiveness of controlling the use of space requires the participation of the community to monitor and provide reports or complaints to the local government if there is a deviation in the use of space in the field. Some space utilization becomes complicated because there is no solution from the start. Handling from the start can be carried out if there is accurate information and is followed up by the local government. This negligence has been a weakness so far that spatial planning goals sometimes go wrong in the utilization of space towards the realization of a safe, comfortable, productive and sustainable space. Therefore, it is deemed necessary to increase the capacity of the community in the form of understanding in order to play an active role in monitoring the use of space in their area with a partner location, namely UPT SMA 5 Makassar City. The problem faced by government officials in Panakkukang District is the lack of community participation in providing responsive information to the local government in following up on problems of irregularities in the use of space according to the existing spatial plan. This problem can be overcome by increasing the community's insight and understanding of spatial planning, the process of controlling space use, and the importance of the active role of the community in providing information if there is a discrepancy in the use of the surrounding space. The purpose of this activity is to increase the insight and knowledge (capacity building) of the community in assisting the government in carrying out the task of controlling the use of space. The target community chosen for this activity is the youth generation (high school students) for the reason that they are relatively easy to understand, effective as agents in conveying their environment, and will soon become a family or part of the community. The results of this activity showed an increase in the level of understanding by 70% related to knowledge of spatial planning, and 71% respectively related to understanding of regulations and the role in spatial control as well as understanding of spatial utilization and control mechanisms.